2021
DOI: 10.3390/ijms22041797
|View full text |Cite
|
Sign up to set email alerts
|

Drugs, Metabolites, and Lung Accumulating Small Lysosomotropic Molecules: Multiple Targeting Impedes SARS-CoV-2 Infection and Progress to COVID-19

Abstract: Lysosomotropism is a biological characteristic of small molecules, independently present of their intrinsic pharmacological effects. Lysosomotropic compounds, in general, affect various targets, such as lipid second messengers originating from lysosomal enzymes promoting endothelial stress response in systemic inflammation; inflammatory messengers, such as IL-6; and cathepsin L-dependent viral entry into host cells. This heterogeneous group of drugs and active metabolites comprise various promising candidates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…These could add to the action of these drugs in alleviating the pathophysiological consequences of SARS-CoV-2. Currently trials are on-going for several drug candidates (Blaess et al, 2021), including some with psychoactive substances like clomipramine (Nobile et al, 2021). However, more detailed clinical studies are required to validate their usefulness as potential drugs against viral infections including COVID-19 in large study populations.…”
Section: Antidepressant Drugs and Covid-19mentioning
confidence: 99%
“…These could add to the action of these drugs in alleviating the pathophysiological consequences of SARS-CoV-2. Currently trials are on-going for several drug candidates (Blaess et al, 2021), including some with psychoactive substances like clomipramine (Nobile et al, 2021). However, more detailed clinical studies are required to validate their usefulness as potential drugs against viral infections including COVID-19 in large study populations.…”
Section: Antidepressant Drugs and Covid-19mentioning
confidence: 99%
“…The author suggested that these compounds could be used off label using either local (inhalative) or systematic administration. Later, the author [ 11 ] developed the repurposing of lysosomotropic drugs (including numerous FIASMAs) in COVID-19 infection.…”
Section: Brief History Of the Studies Of Fiasmas In The Sars-cov-2 Infectionmentioning
confidence: 99%
“…The second point to be considered is the choice of the FIASMAs and the duration of their prescription within the study. Indeed, this latter parameter influences the accumulation in pulmonary tissue, and more specifically in lysosomes, to achieve the desired inhibition of acid sphingomyelinase [ 11 ]. The highest accumulation in plasma and also into the lysosome compartments (i.e., called steady-state) requires around 7 times the apparent elimination half-life of the drug to occur.…”
Section: Update (16 June 2021) On Studies With Fiasmas In the Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains two functional subunits: The S1 subunit binds to and interacts with the cell-surface receptors, while the S2 subunit mediates membrane fusion (2,3). Alongside S protein binding, cleavage of S proteins at the polybasic cleavage-sites by the membrane-associated Transmembrane Protease Serine 2 (TMPRSS2) and the lysosomal cysteine protease Cathepsin-L facilitates membrane-fusion and virus entry at the cellular endosomes (4,5). The released viral genomic RNA (gRNA), which carries a cap-structure and a polyA-tail, serves as a direct template for the cellular ribosomemediated translation of the two large ORFs: ORF1a and ORF1b.…”
Section: Sars-cov2 Replication Cyclementioning
confidence: 99%